Development of polymorphic simple sequences repeats markers from whole gene resequencing data comparison of 68 Oncorhynchus mykiss - Ma, Haibing; Huang, Tianqing; Liu, Enhui; Wang, Gaochao; Gu, Wei; Xu, Gefeng (Frontiers in Marine Science, 2024)
Rainbow trout (Oncorhynchus mykiss) is a significant cold-water fish farmed in China. Currently, most molecular marker-assisted breeding applications in rainbow trout rely on SSR markers. Although many rainbow trout SSR markers have been developed, methods for mining many polymorphic SSR markers from the genome and identifying them efficiently and rapidly are still lacking. For this reason, this study used in silico simulation method to rapidly develop a large number of polymorphic SSR markers quickly. A total of 354,613 SSR loci with two to six nucleotide repeat motifs were mined from 32 chromosomes of the rainbow trout reference genome using GMATA. The chromosome sequences of the reference genome were then aligned to the whole genome sequencing data (10×) of 68 rainbow trout samples. In silico genotyping was performed using the HipSTR programme to compare and count the variation in the number of repeats of the motifs of the SSR loci in the samples. The loci with high deletion rates and monomorphism were discarded, while those with more than one non-reference allele were kept. The final set of polymorphic SSR loci screened was 78,828. Finally, 4,821 SSR loci were selected with more than 3 alleles and no deletion in all rainbow trout samples and were physically mapped. The average polymorphic information content of these loci was 0.692, indicating high levels of polymorphism. These SSRs were utilized to analyse the genetic diversity and population structure of the 68 rainbow trout samples. The results showed that these 68 samples were divided into two groups. These newly discovered polymorphic SSR markers will provide valuable information for evaluating the construction of rainbow trout family lines for genetic diversity and improvement.